2017
DOI: 10.1080/13691058.2017.1367421
|View full text |Cite
|
Sign up to set email alerts
|

What motivates serodiscordant couples to prevent HIV transmission within their relationships: findings from a PrEP implementation study in Kenya

Abstract: With the planned scale-up of pre-exposure prophylaxis (PrEP) for HIV prevention among serodiscordant couples in resource-limited settings, gaining an understanding of what motivates serodiscordant couples to prevent HIV is critical. We conducted 44 semi-structured, in-depth individual or couple interviews with 63 participants (33 HIV-infected and 30 HIV-uninfected participants) enrolled in a prospective implementation study of oral antiretroviral-based prevention in Kisumu, Kenya. Transcripts were iteratively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 33 publications
2
16
0
Order By: Relevance
“…The experiences of couples who are not research participants, have long lived with serodiscordance, do not remain together, and/or whose nationalities and cultural backgrounds differ may not be the same. The similarities observed for Kenyan serodiscordant couples suggests the patterns described here are not characteristic only of Ugandans, however. Finally, the possibility that the qualitative interview data may be subject to social desirability bias, in which interviewees provide responses they believe to be “correct,” or “what the interviewer wants to hear,” must be acknowledged.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The experiences of couples who are not research participants, have long lived with serodiscordance, do not remain together, and/or whose nationalities and cultural backgrounds differ may not be the same. The similarities observed for Kenyan serodiscordant couples suggests the patterns described here are not characteristic only of Ugandans, however. Finally, the possibility that the qualitative interview data may be subject to social desirability bias, in which interviewees provide responses they believe to be “correct,” or “what the interviewer wants to hear,” must be acknowledged.…”
Section: Discussionmentioning
confidence: 50%
“…HIV serodiscordant couples participating in this qualitative study reported PrEP strengthened relationships by reducing fear of HIV transmission and increasing sexual intimacy. These themes have also been reported in other couples‐focused analyses , and among MSM PrEP users, most of whom are not in a known HIV serodiscordant relationship . In this analysis, we draw out the larger significance of couples’ views, to consider their implications for future PrEP demand creation initiatives.…”
Section: Discussionmentioning
confidence: 66%
“…Despite the observed successes of PNS, the study highlighted challenges, consistent with other studies. The barriers to uptake of partner testing have included mistrust of public health workers, stigma and shame of knowing that they have been diagnosed with HIV and fear of notifying their partners . The study further showed that some partners expressed concerns about confidentiality and stigma.…”
Section: Discussionmentioning
confidence: 90%
“…In a context of limited power over decisions over sex and condom use, female-controlled interventions such as female condoms and PrEP are essential to prevent HIV acquisition during pregnancy. A recent qualitative study in Kenyan serodiscordant couples found that couples held the HIV-infected individual as responsible for HIV prevention and women accountable for prevention methods such as condom use [ 22 ].Understanding what motivates pregnant and breastfeeding women to use PrEP to prevent HIV is critical. Like Patel et al’s study, we agree that HIV prevention interventions must address important gender norms that may pose barriers to PrEP uptake.…”
Section: Discussionmentioning
confidence: 99%